NARASI MODERASI BERAGAMA DALAM BUKU SKI TINGKAT MI - Abdul Gani Jamora Nasution; Defi Antika; Nurul Sakinah; Harits Heriadi (Pusat Riset dan Inovasi Nasional, 2022)
Religious moderation is one of the programs prioritized by the government to build a harmonious religious life within the framework of national and state life. Religious moderation based on the definition given by the ministry of religion through his book which he compiled entitled religious moderation means confidence in the essence of the teachings of the religion he adheres to, while continuing to share the truth as far as religious interpretation is concerned. The values ​​of religious moderation education that are internalized in SKI books at the elementary school level are the values ​​of tolerance, caring for others, mutual affection for others, and being an honest and respectful person to parents and teachers. The type of research used is library research with a qualitative approach. Qualitative approach is research that is used to examine the condition of natural objects. Library research (library research) is a study carried out by collecting information and data needed through various types of materials or materials in the library including; reference books, similar research results, articles, notes, and journals that are relevant to the research problem.